Continuous Hydrogenation of L‐Arabinose and D‐Galactose in a Mini Packed‐Bed Reactor1. Issue 11 (13th October 2017) - Müller, Anne; Hilpmann, Gerd; Haase, Stefan; Lange, Rüdiger
Abstract: The continuous hydrogenation of a mixture of L ‐arabinose and D ‐galactose over a Ru/C catalyst was investigated in a miniaturized packed‐bed reactor. The reaction is one important step of the transformation of the naturally occurring hemicellulose arabinogalactan into valuable sugar alcohols. Process intensification was accomplished by reducing the reactor dimensions to a few millimeters; thus leading to better mass and heat transfer performance. The effects of temperature, pressure, and liquid flow rate on the yield and by‐product formation are discussed. Based on a kinetic model derived from batch experiments, a model of the continuous reactor was developed and used for scale‐up purposes. Abstract : Sugar alcohols are versatile molecules that can be produced from renewable feedstocks. A kinetic model for the hydrogenation of L ‐arabinose and D ‐galactose over a ruthenium catalyst is reported. Experimental studies in a continuous miniaturized packed‐bed reactor show that process safety and volumetric space‐time‐yield can be enhanced compared with a conventional slurry batch reactor.